Die Bestattungsgruben in Bat - Schmidt, Conrad, (Arabia orientalis ;, 2020)
A comprehensive study of two Umm an-Nar (2700-2000 BC) burial pits from the UNESCO World Heritage site Bat in the Sultanate of Oman, excavated 2010-2012. Each burial pit represents one of the largest closed finds of the Early Bronze Age in the region, including beads and other items of personal adornment, as well as pottery and human bones.